(untitled) (Ágora Journal, 2021)
To analyze the historicity of literature studies of testimony, we divided this article into two parts: 1) we raised references to the concept of testimony by intellectuals and scholars; 2) we studied how a reading sphere was organized from the notion of the concept of “witness literature” in Brazil. This second movement is carried out considering that in newspapers and cultural magazines in the last years of the 1990s, a group of specialized critics can be identified that began to deal with the literature of Primo Levi and other witnesses from the concentration camps. Our objective is to reflect on the formation of Testimony Literature studies and the dilemmas faced by intellectuals, such as the narrative limit in the face of traumatic experience.